Four attachment-based categories of emotion regulation in adolescent psychic troubles - Marion Robin; Marion Robin; Luc Surjous; Luc Surjous; Jean Belbèze; Jean Belbèze; Lucile Bonnardel; Claire Lamas; Jérôme Silva; Victoire Peres; Maurice Corcos; Maurice Corcos (Frontiers in Psychology, 2023)
IntroductionEmotion regulation is altered in many psychiatric disorders in adolescence, but the understanding of mechanisms that underlie this alteration is still poor.MethodsThe PERCEPT study explores alexithymia, empathy, facial emotion recognition (FER) and defence mechanisms in a sample of adolescents in psychiatric care (n = 61, 74% of girls, mean age = 15.03 y.o.), in relation with participants’ attachment styles.ResultsResults revealed correlations between attachment dimensions and all of the emotion regulation variables, suggesting that attachment modalities have functional links with emotional regulation at its different levels: FER accuracy was inversely correlated with avoidant attachment, while affective empathy, difficulty in identifying feelings (alexithymia) and immature as well as neurotic defence mechanisms were positively correlated with anxious attachment. Moreover, attachment categories delineated distinct emotional perception profiles. In particular, preoccupied attachment included adolescents with the highest levels of facial emotion perception (sensitivity and accuracy) and of affective empathy, whereas detached attachment included adolescents with the lowest levels of these variables. Neurotic defence mechanisms and difficulty to identify feelings were correlated with preoccupied attachment; immature defence mechanisms and difficulty to describe feelings to others characterized fearful attachment.DiscussionThese results suggest that attachment categories underlie emotion regulation processes in psychiatric disorders in adolescence. Theoretical and clinical implications are discussed.